STRATEGIES FOR STRENGTHENING TEACHER INTEGRITY TO IMPROVE THE QUALITY OF EDUCATION AT AL-AZHAR SBP JUNIOR HIGH SCHOOL - Iskandar, Nanang; Sabila, Nurina Wulan; Supendi, Pepen (LP2M IAI Al-Khairat Pamekasan, 2025)
This research examines the challenges educators face in maintaining ethical standards and fostering institutional effectiveness amidst growing complexities in the education sector. A qualitative research design was adopted, utilizing in-depth interviews and document analysis to gather comprehensive data on teachers' perceptions and implementations of professional ethics within school management frameworks. Findings indicate several critical barriers, such as inadequate institutional support, insufficient professional development programs, and external socio-political pressures that impede the consistent practice of ethical teaching. Moreover, the study reveals a gap between theoretical knowledge of professional ethics and its practical application in daily teaching activities. Recommendations include the establishment of collaborative support networks among educators, the development of ongoing professional capacity-building programs, and the implementation of robust institutional policies that prioritize ethical practices. Additionally, fostering moral resilience through reflective practice and mentorship programs can help teachers navigate ethical dilemmas effectively. This study contributes to the broader discourse on educational quality by highlighting the essential link between teacher professionalism, ethical standards, and institutional accountability. Ultimately, it underscores the need for schools and educational policymakers to create supportive environments where educators can thrive ethically and professionally, ensuring a sustainable, high-quality education system that benefits all stakeholders.